Газоразрядные лазеры терагерцевого диапазона - Дзюбенко, М.И.; Каменев, Ю.Е.; Радионов, В.П. (Радіофізика та електроніка, 2017)
В работе приведены результаты экспериментальных и теоретических исследований газоразрядных лазеров терагерцевого диапазона, обобщены многочисленные исследования особенностей их работы. Представлен ряд новых разработок, направленных на повышение эффективности и расширение функциональных возможностей газоразрядных терагерцевых лазеров. Разработаны новые способы накачки газоразрядных лазеров. Предложены новые технические решения, позволяющие повысить мощность и КПД лазера благодаря оптимизации процесса синтеза активного вещества и устранению негативного влияния побочных продуктов синтеза. Разработаны методики моделирования формы импульсов лазерной генерации в лазерах с накачкой импульсным током и переменным током низкой частоты. Предложены и созданы новые типы лазерных резонаторов и новые разновидности зеркал. Разработаны лазерные резонаторы с зеркалами, не требующими точной юстировки. Предложены частично прозрачные зеркала в виде плоских периодических структур, сочетающие в себе функции вогнутых зеркал и фокусирующих линз, что позволяет снизить дифракционные потери лазерного излучения. Представлены резонаторы с новыми принципами плавной регулировки вывода излучения. Разработаны много-частотные лазеры и системы плавной регулировки частоты их излучения без использования частотно-измерительной аппаратуры. Все это позволило улучшить параметры терагерцевых лазеров и расширить область их применения. Представлены некоторые сферы применения ТГц-лазеров, в частности в медицинских целях и в области измерений. Разработаны новые способы измерения показателей преломления различных веществ и материалов в терагерцевом диапазоне с использованием разработанных лазеров. В роботі наведено результати експериментальних і теоретичних досліджень газорозрядних лазерів ТГц-діапазону, узагальнено численні дослідження особливостей їх роботи. Представлено низку розробок, спрямованих на підвищення ефективності та розширення функціональних можливостей газорозрядних ТГц-лазерів. Розроблено нові способи накачування газорозрядних лазерів. Запропоновано нові технічні рішення, що дозволяють підвищити потужність і ККД лазера завдяки оптимізації процесу синтезу активної речовини та усуненню негативного впливу побічних продуктів синтезу. Розроблено методики моделювання форми імпульсів генерації в лазерах з накачуванням імпульсним струмом і змінним струмом низької частоти. Запропоновано та створено нові типи лазерних резонаторів і нові різновиди дзеркал. Розроблено лазерні резонатори з дзеркалами, що не вимагають ретельного юстування. Запропоновано частково прозорі дзеркала у вигляді плоских періодичних структур, що поєднують в собі функції увігнутих дзеркал і фокусуючих лінз, що дозволяє знизити дифракційні втрати лазерного випромінювання. Представлено резонатори з новими принципами плавного регулювання виведення випромінювання. Розроблено багаточастотні лазери і системи плавного регулювання частоти їх випромінювання без використання частотовимірювальної апаратури. Все це дозволило поліпшити параметри ТГц-лазерів і розширити область їх застосування. Представлено деякі галузі застосування ТГц-лазерів, зокрема в медичних цілях і в області вимірювань. Розроблено нові способи вимірювання показників заломлення різних речовин і матеріалів у ТГц-діапазоні з використанням створених лазерів. The results of experimental and theoretical studies of gas-discharge THz-lasers, and numerous studies of the features of their work have been summarized in the paper. A number of new developments aimed at increasing the efficiency and expanding the functionality of gas-discharge terahertz lasers have been presented. New methods of pumping gas-discharge lasers, which were developed, have been presented. We have proposed new technical solutions which allow increasing the power and efficiency of the laser by optimizing the synthesis of the active substance and eliminating the negative impact of synthesis by-products. New methods for modeling the shape of laser pulses in lasers pumped with pulsed current and alternating low-frequency current have been presented. New types of laser resonators and new varieties of mirrors have been proposed and created and they have been presented in this work. Laser resonators with mirrors that do not require accurate alignment have been developed. Partially transparent mirrors, in the form of flat periodic structures that combine the functions of concave mirrors and focusing lenses, have been proposed. These mirrors can reduce the diffraction loss of laser radiation. Resonators with new principles of smooth regulation of radiation output from them, have been presented. Multifrequency lasers have been developed. Systems for the smooth adjustment of the frequency of electromagnetic laser radiation, in which adjustment is carried out without the use of frequency measuring equipment, have been designed for these lasers. All these new developments, presented here, have made it possible to improve the parameters of terahertz lasers and to expand their field of application. Some applications of THz lasers, in particular medical applications and in the field of measurement have been presented. New ways of measuring the refractive indices of various substances and materials in the THz range, using the developed lasers, have also been presented in this work.